1996
DOI: 10.1210/jcem.81.3.8772595
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hypopituitarism on life expectancy.

Abstract: One hundred and seventy-two patients with partial or complete hypopituitarism diagnosed between 1967 and 1994 were studied retrospectively. Those with acromegaly or Cushing's disease were excluded. One hundred and two patients were male (median age at, diagnosis, 53 yr; range, 12-78 yr) and 70 female (median age at diagnosis, 51 yr; range, 1-74 yr). In 131 patients the cause of hypopituitarism was a pituitary tumor or the effects of its treatment, as the majority underwent surgery and/or radiotherapy. In 22, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
214
5
5

Year Published

2000
2000
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(245 citation statements)
references
References 12 publications
12
214
5
5
Order By: Relevance
“…However, after correction for pituitary dysfunction, this association was no longer significant, suggesting that the observed increase in premature mortality is mediated by RT‐induced hypopituitarism rather than an independent effect of RT itself. These data are consistent with findings from Tomlinson and other older studies,16, 36 as well as the more recent van Varsseveld and Oxford studies 17, 35. There was a trend towards an increased risk of cerebrovascular death compared to nonirradiated patients, but this did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 89%
“…However, after correction for pituitary dysfunction, this association was no longer significant, suggesting that the observed increase in premature mortality is mediated by RT‐induced hypopituitarism rather than an independent effect of RT itself. These data are consistent with findings from Tomlinson and other older studies,16, 36 as well as the more recent van Varsseveld and Oxford studies 17, 35. There was a trend towards an increased risk of cerebrovascular death compared to nonirradiated patients, but this did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 89%
“…These results were similar to those in normal aging males [21,22], and patients with diabetes [23,24]. Unlike other studies [2,4,25], our studied patients with hypopituitarism had lower HOMA-IR than the healthy control group (HOMA-IR, 2.22 ± 0.22 vs.…”
Section: Discussionsupporting
confidence: 89%
“…Epidemiological studies have shown that this abdominal obesity is a risk factor for development of metabolic abnormalities leading to cardiovascular complications [4,5]. In studies in Japanese adult patients with GHD it has been shown that there is an increased risk of cardio-and cerebro-vascular morbidity and mortality compared to the normal population [6][7][8], similar to that previously shown in Caucasian patients [5,[9][10][11].…”
supporting
confidence: 64%